2007
DOI: 10.1063/1.2748443
|View full text |Cite
|
Sign up to set email alerts
|

Polymer induced drag reduction in exact coherent structures of plane Poiseuille flow

Abstract: Nonlinear traveling waves that are precursors to laminar-turbulent transition and capture the main structures of the turbulent buffer layer have recently been found to exist in all the canonical parallel flow geometries. The present work examines the effect of polymer additives on these "exact coherent states" (ECS) in the plane Poiseuille geometry, using the FENE-P constitutive model for polymer solutions. In experiments with a given fluid, Reynolds and Weissenberg numbers are linearly related (i.e. Wi/Re = c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
59
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 105 publications
(197 reference statements)
11
59
2
Order By: Relevance
“…3 The relationship between quasi-streamwise vortices and polymer force was comprehensively illustrated for exact coherent states that mirror the basic structure of near-wall turbulence. 4,5 Recent studies on hairpin vortices originating from the near-wall regions confirmed that polymers effectively apply a negative torque to vortices. 6 The drag reduction results from the dramatic damping and reduction in numbers of quasi-streamwise vortices, the very cause of the dramatic increase in skin-friction drag between laminar and turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…3 The relationship between quasi-streamwise vortices and polymer force was comprehensively illustrated for exact coherent states that mirror the basic structure of near-wall turbulence. 4,5 Recent studies on hairpin vortices originating from the near-wall regions confirmed that polymers effectively apply a negative torque to vortices. 6 The drag reduction results from the dramatic damping and reduction in numbers of quasi-streamwise vortices, the very cause of the dramatic increase in skin-friction drag between laminar and turbulent flows.…”
Section: Introductionmentioning
confidence: 99%
“…Graham and co-workers [13][14][15][16] have extensively studied modifications of the exact coherent state in viscoelastic flows. They suggested that viscoelasticity weakens the streamwise vortices and that the coherent structures can be suppressed entirely if the elastic effects are sufficiently large.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, at Wi = 29 the peak value of α yy , which is closely associated with streamwise vortex suppression [12,16,17], drops from about 210 in active turbulence to about 5 during hibernation, a 40-fold reduction. These results suggest that hibernation should be very similar in the Newtonian and viscoelastic cases.…”
mentioning
confidence: 99%